The Effectiveness of Group Therapy In Improving Self-Esteem Among Female Students Of The Psychology Faculty At Univeristy X In Bandung - Rifqi Farisan Akbar; Pratidina Ekanesia; Prinska Damara Sastri (Westscience Press, 2023)
People who have low self-esteem when they fail to do something, they will see themselves as worthless individuals, feel that their lives are meaningless, hopeless and affect themselves in their behavior (Murk, 2006). This is termed the word self-esteem. When students are required to make presentations, they often display symptoms such as cold hands, trembling voice, unstructured sentences, decreased volume, racing heart, and unable to speak when asked, feeling unable to think. This behavior is often seen as an individual with low self-esteem characteristics (Coopersmith, 1967). In order to increase self-esteem, there are various kinds of interventions that can be done, one of which is group therapy. Group therapy or counseling itself has advantages in terms of helping people who have experience with emotional, relational, or psychological difficulties (Virginia A. Brabender et al, 2004). The research design used was experimental research with a One-group pretest-posttest design. The tool for measuring self-esteem is the Self-Esteem Inventory Scale from Coopersmith (1967). The sampling technique used was purposive sampling. The results of the intervention show that there is an effect of giving group therapy on increasing self-esteem.